Peran Administrasi Supervisi Pendidikan Kontemporer - Ananda Tazkia Ramadhani; Miftahir Rizka; Dwi Nazwa Adisti; Anggini, Anggini; Andini Putri; Putri Diana (Harmoni Pendidikan : Jurnal Ilmu Pendidikan, 2025)
Educational supervision administration has undergone major changes to adapt to the challenges and dynamics of education today. Changes in the curriculum, the application of digital technology, and increasing demands for accountability and quality of education services require a more adaptive, collaborative and data-driven supervision model. Previously top-down supervision has shifted to a more participatory approach, focusing on teachers' professional development and continuous improvement of learning quality. This study highlights the important role of educational supervision administration in the contemporary context, with an emphasis on modern supervision principles such as coaching, mentoring and clinical supervision. In addition, the use of information technology is a key factor in improving the effectiveness of the supervision process. Various studies have shown that modern supervision approaches significantly contribute to improving teacher competencies and student learning outcomes (Rahman, 2020; Sari & Widodo, 2021; Nurlaila, 2022). Therefore, educational supervision administration must continue to evolve with the times, while upholding the principles of ethics, professionalism and collaboration.